STRATEGI GURU DALAM MENGEMBANGKAN SIKAP SPIRITUAL PESERTA DIDIK MELALUI KURIKULUM MERDEKA DI MIN 1 KOTA CILEGON - Fadilawati, Andini; Nurhasanah, Ana; Pribadi, Reksa Adya (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe the teacher's strategies in developing students' spiritual attitudes within the Merdeka curriculum. The research used a qualitative descriptive approach, with 55 participants consisting of 1 school principal, 1 teacher, and 26 students from class V Al-Khaizini, as well as 1 teacher and 26 students from class V Al-Jayyani. The data collection tools used were field notes and interview guidelines, with data analysis conducted using the Miles & Huberman model. The findings show that the learning strategies implemented by the teacher to enhance students' spiritual attitudes were carried out effectively, following the strategies outlined in the teaching module. The enthusiasm for studying religious teachings improved students' understanding and interest in deepening their knowledge of religion. Discipline at MIN 1 Cilegon was strengthened through verbal warnings, additional tasks, and grade reductions for those lacking discipline, as well as adherence to religious commandments.